Belt and Road investments in Serbia: Is China a new saviour or a new threat? - Vladan Ivanović; Katarina Zakić (Međunarodni Problemi, 2023)
Versatile political and institutional cooperation between Serbia and China recently spurred the dynamic development of economic relations between the two countries. Those progressed quickly, especially due to Serbia’s participation in the format China-Central and Eastern European countries and the Belt and Road initiative. it caused changes in economic relations between China and Serbia in three directions: changes in trade patterns, the volume of loans, and the inflow of Chinese investments. This article focuses on the Chinese Belt and Road investments (foreign direct investments, acquisitions, and joint ventures) in Serbia while using qualitative along with descriptive statistical analysis. The authors analysed the type of companies, value of investments, and industries in which Chinese companies invested capital in the period 2014-2022. Research findings indicate an increase in bilateral trade, especially in export, after the Chinese investments have been made. The value of Chinese investment has grown over time, with a relatively high concentration in the automotive industry and a presence in rather few industries. The first investments were realized by state-owned enterprises and, in recent times, by private-owned companies. The authors indicate that while China’s role in Serbian economic development is increasing, it should not be categorized either as a saviour or a threat, but as a rather important economic partner of Serbia whose influence in Serbia is increasing. However, the interplay between China and Serbia, determined by the interests of both sides as well as the capabilities of Serbia to design appropriate institutional and policy frameworks will determine the contribution of Chinese investments to Serbian economic development in the future.